NEUTRALITY OR NUANCE? MAPPING JUDGMENT AND ENGAGEMENT IN JOURNALISTIC DISCOURSE ON TEENAGE PREGNANCY - Da Costa, Fransiscus Joseph Izhak; Cahyono, Setyo Prasiyanto (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study examines the extent to which journalistic objectivity is maintained or nuanced in Polly Toynbee’s article on teenage pregnancy, published by The Guardian (https://www.theguardian.com, accessed July 2025). Employing Martin and White’s (2005) Appraisal Framework, the analysis focuses on two key subsystems: Judgment (evaluations of people’s behavior, ethics, and capacity) and Engagement (how other perspectives are acknowledged or suppressed). The study adopts a qualitative content analysis approach with manual coding of appraisal instances, supported by frequency counts to quantify evaluative patterns. The findings revealed that the discourse surrounding teenage pregnancy is far from neutral. A total of 29 Judgement Attitude instances were identified. Of these findings, 64.29% (18 instances) were negative propriety judgments, often directed at the Conservative Party, portraying them as morally neglectful, indifferent, or even hostile to the needs of socially disadvantaged communities. On the other hand, positive judgment (17%) was associated with the New Labour government, and acknowledging the eagerness of a head of social unit. These are linguistically framed as responsible, evidence-based, and socially just, reinforcing a moral contrast between political ideologies. In terms of Engagement, 99 instances were noted. A significant 62.62% (62 instances) were monoglossic or contractive, indicating that Toynbee frequently limits alternative perspectives. The remaining 37.37% (37 instances) of dialogic expansion appear mainly in rhetorical constructions or hypothetical examples, such as imagining how disadvantaged girls perceive their futures. This heavy reliance on negative judgment and contracted engagement suggests that Toynbee uses journalistic discourse not merely to report on teenage pregnancy, but to frame it as a socio-political issue rooted in inequality, institutional failure, and class-based neglect. Overall, the findings show that Toynbee’s discourse, while seemingly objective, is deeply infused with evaluative meaning. This reveals how journalistic texts, particularly those addressing complex social issues like teenage pregnancy, function as sites of ideological negotiation, shaping public attitudes through both explicit judgment and subtle engagement.